2004
DOI: 10.1111/j.1365-3040.2004.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

Thylakoid membrane responses to moderately high leaf temperature in Pima cotton

Abstract: Photosynthesis is inhibited by high temperatures that plants are likely to experience under natural conditions. Both increased thylakoid membrane ionic conductance and ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) deactivation have been suggested as the primary cause. The moderately heat-tolerant crop Pima S-6 cotton ( Gossypium barbadense ) was used to examine heat stressinduced inhibition of photosynthesis. Previous field-work indicated that moderate heat stress ( T = 35-45 ∞ ∞ ∞ ∞ C) is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
228
1
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(255 citation statements)
references
References 58 publications
18
228
1
8
Order By: Relevance
“…Increased permeability has been found to occur particularly at high temperatures, concurrently with denaturation of membrane lipids (Bukhov et al, 1999;Schrader et al, 2004;). The increased membrane permeability of heat-treated samples can be due to conformational changes of membrane lipids, opening of ion channels, or changes in lipid-lipid interactions (Santarius, 1980).…”
Section: Electrochromic Shift and Membrane Conductancementioning
confidence: 99%
See 1 more Smart Citation
“…Increased permeability has been found to occur particularly at high temperatures, concurrently with denaturation of membrane lipids (Bukhov et al, 1999;Schrader et al, 2004;). The increased membrane permeability of heat-treated samples can be due to conformational changes of membrane lipids, opening of ion channels, or changes in lipid-lipid interactions (Santarius, 1980).…”
Section: Electrochromic Shift and Membrane Conductancementioning
confidence: 99%
“…The oldest and most widely accepted idea is that isoprene stabilizes chloroplast membranes (Sharkey and Singsaas, 1995). Thylakoid membranes become leaky at high temperature (Pastenes and Horton, 1996;Bukhov et al, 1999;Schrader et al, 2004;. It was suggested that the positive effect of isoprene might be due to the hydrophobic nature of the molecule, the localization of isoprene synthase enzyme near the thylakoid membranes (Wildermuth and Fall, 1998;Schnitzler et al, 2005), and the high octanol/water partitioning coefficient (Copolovici and Niinemets, 2005).…”
mentioning
confidence: 99%
“…We also observed decreases in 12qL and NADP-MDH activation at high temperature (Figs. 3 and 4), implying that the heat-induced decline in photosynthesis would be also affected by, at least, the redox status of the stroma (Schrader et al, 2004;Sharkey, 2005).…”
Section: Activation State Of Nadp-malate Dehydrogenasementioning
confidence: 99%
“…Salvinia exposed to Cr and Zn did not exhibit a significant increase in NADP-MDH activity indicating that metal stress does not affect stromal status as adequate levels of NADPH and other reducing equivalents are maintained for CO 2 assimilation. It is supposed that closure of the malate valve under stress also prevents drainage of excess reducing equivalents from the chloroplast, hence preventing the oxidation of stroma (Scheibe and Stitt, 1988;Schrader et al, 2004). The effect of ARC and redox state on the enzyme activation has also been reported (Backhausen et al, 2000).…”
mentioning
confidence: 99%